Regulasi Emosi dan Parenting Stres Pada Ibu Bekerja - Fathana Gina; Yulia Fitriani (Jurnal Kajian Ilmiah, 2022)
This study aims to empirically examine the contribution of emotional regulation to parenting stress on working mothers. The hypothesis proposed is that emotion regulation is able to predict parenting stress on working mothers. The subjects of this study were working mothers who had children with a total number of 318 mothers. The study uses two measuring instruments, Emotion Regulation Scale (Gross and John, 2003) with reliability coefficient 0.831 and Parenting Stress Scale (Berry and Jones, 1995) with reliability coefficient 0.71. Data analysis using simple regression techniques and processed using SPSS 23 for Windows. Hypothesis test results show that emotion regulation is able to predict parenting stress significantly with F = 15.838 and p = 0.000 (p <0.001). The R square value of 0.048 means that regulation of emotion is able to contribute effectively to parenting stress by 4.8%, while 95.2% is influenced by other factors.